Attitudes and motivation of primary school learners in learning English as a second language: a case study / Nurnazihah Abdullah@Nalam Ali - Abdullah@Nalam Ali, Nurnazihah (2015)
Learning of English as Second Language (ESL) in Malaysia has always been a controversial issue. The deterioration of English standard beseeched this study.Lack of motivation and the negative attitude among learners in learning English has become a major concern among the educators. Thus, this case study sought to scrutinize the Attitudes and Motivation of Primary School Learners towards Learning English as a Second Language. The aims of this study are to determine the attitudes of the primary school learners toward learning English and to identify the motivational factor(s) that influenced the learners learning of English as a second language. Thirty-five (35) Year Four pupils of SK Matang, Padawan Kuching were involved. The research design is a case study. Data were analyzed quantitatively and qualitatively, with descriptive analysis. The findings show that the learners were very positive towards learning English. This study also revealed that these learners were greatly influenced by both the extrinsic and intrinsic motivational factors in learning English. The prominent influential extrinsic factors are parents, family members, friends and teachers. On the other hand, the interest in learning English language, image as the successful learners and the challenges of problem solving in learning the language are the intrinsic motivational factors.